Preventing suicide by restricting access to Highly Hazardous Pesticides (HHPs): A systematic review of international evidence since 2017. - Bruna Rubbo; Chao-Ying Tu; Lucy Barrass; Shu-Sen Chang; Flemming Konradsen; David Gunnell; Michael Eddleston; Chris Metcalfe; Duleeka Knipe (PLOS Global Public Health)
Suicide is a leading cause of death worldwide. A previous systematic review showed that regulations limiting access to highly hazardous pesticides (HHPs) were successful in preventing suicides. As the WHO strongly supports regulation of pesticides, we aimed to update and strengthen the evidence on the effectiveness of HHP bans. We conducted a systematic review by searching MEDLINE, Embase, and PsycINFO databases in March 2024 for manuscripts published since 2017 that investigated the effects of regulatory changes limiting access to HHPs on pesticide suicide, at the population level. Two reviewers independently screened titles and abstracts, and extracted data using a standardized form, defined a priori. The study protocol was registered in PROSPERO (CRD42023441247). All nine studies in six Asian countries showed reductions in pesticide suicide rates following HHP bans (range 28.0% to 91.9%), of which six applied time series analyses to account for trends prior to the intervention (reductions in pesticide suicide rates ranged 28.0% to 60.5%). Only five studies assessed overall suicides; of those, four reported decreases in overall suicide rates following the intervention, of which three used time series analysis (range 7.0% to 45.1%). Only one study had a low risk of bias in all domains, with five studies having high risk of bias in at least one of the domains. Restricting access to HHPs leads to declines in both pesticide and overall suicide rates. Findings from this and the previous systematic review provide strong evidence to governments and public health officials that are considering implementing bans on HHPs in order to reduce suicides. However, this review only covered studies published since 2017 and there is a need for data from other regions to investigate the generalisability of this approach.